La calistenia en la fuerza relativa en adultos jóvenes. - Curisaca Lopez, Cristofer Alexander (2025)
The present investigation consisted of determining the development of relative strength through the practice of calisthenics in young adults from the "Jaguares" sports academy in the city of Riobamba. The respective strength test was applied to measure maximum and relative strength through the practice of calisthenics movements. A pre- and post-evaluation of the calisthenics intervention program was conducted, which was scheduled to last 12 weeks. A field, correlational and transversal research method was used, with a quasi-experimental design; The population to be taken into account is 10 young adults from the Jaguares sports academy, the techniques were observation and a 1RM bench press test, which allowed us to know the level of maximum strength that young adults have. For a test of less than 30 cases, we proceed to carry out the Shapiro-Wilk statistical analysis, given that our sample consists of 10 cases. In the normality test implemented by Shapiro. The pre-test shows a significance greater than 0.05, resulting in a result of < 0.38. The pre-test shows a significance greater than 0.05, resulting in a result of > 0.21. Therefore, it is established that the data do not have a normal distribution, which leads us to use a parametric statistical test, such as the T-student, for paired samples. Through the application of the T-student for paired tests in the present study, a significant value of 0.00 was obtained for bilateral significance. This value is within the pre-established margin of error of 5%, corresponding to a P value of 0.05. Therefore, the alternative hypothesis that postulates that the practice of calisthenics exerts a positive influence on the relative strength of young adults is accepted, thus rejecting the negative hypothesis